(untitled) (Tábano, 2025)
This paper examines the interventions of philosophy in the programs of Communication Theory and Theory and Analysis of Literary Discourse, two subjects belonging to the Literature degree (Faculty of Philosophy and Letters, UCA). Specifically, three thematic cores are reviewed (the discursive construction of otherness, hermeneutics and deconstruction as reading practices and the delimitation of the boundaries between fiction and reality) that arise in literary studies and demand philosophical responses, establishing a back and forth movement between both disciplines. Finally, we postulate the close relationship between poetry and the philosophy developed by authors such as Derrida, Agamben and Lacoue-Labarthe at the turn of the 20th to the 21st century.